2022
DOI: 10.1186/s13287-022-02893-1
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells-derived exosomes for treating traumatic pancreatitis in rats

Abstract: Background The therapeutic and protective effects of human umbilical cord mesenchymal stem cells-exosomes (hucMSC-Exs) on traumatic pancreatitis (TP) remain unknown. Here, we established a rat model of TP and evaluated and compared the therapeutic effects of hUC-MSCs and hucMSC-Exs. Methods HucMSC-Exs were obtained by ultracentrifugation and identified using transmission electron microscopy and western blot analysis. TP rats were treated by tail ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Approximately 1 mL normal saline was injected via the tail veins of rats. In the TP group, the modelling approach is presented in a previous study 4 . In the TP+ ucMSC‐Ex + rapamycin group, a TP model was established for this group.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 1 mL normal saline was injected via the tail veins of rats. In the TP group, the modelling approach is presented in a previous study 4 . In the TP+ ucMSC‐Ex + rapamycin group, a TP model was established for this group.…”
Section: Methodsmentioning
confidence: 99%
“…Human umbilical cord mesenchymal stem cells (hucMSC) have been frequently recognized for their capacity for self-renewal and multilineage differentiation, particularly for the bioactive chemicals they contain for tissue repair and the management of inflammation [ 177 , 178 ]. Han et al discovered that hucMSC-derived exosomes showed a remarkable tissue regeneration potential in rats suffering from traumatic pancreatitis (trauma-induced non-infectious AP) [ 179 ]. In particular, hucMSC-Evs injected intravenously could colonize injured pancreatic tissue and inhibit inflammatory response and apoptosis of acinar cells, promoting damaged tissue repair [ 179 ].…”
Section: The Therapeutic Potential Of Exosomes In Ap and Associated Alimentioning
confidence: 99%
“…Han et al discovered that hucMSC-derived exosomes showed a remarkable tissue regeneration potential in rats suffering from traumatic pancreatitis (trauma-induced non-infectious AP) [ 179 ]. In particular, hucMSC-Evs injected intravenously could colonize injured pancreatic tissue and inhibit inflammatory response and apoptosis of acinar cells, promoting damaged tissue repair [ 179 ]. A less frequent consequence of AP is myocardial injury, which is challenging to treat and has a high death rate [ 180 ].…”
Section: The Therapeutic Potential Of Exosomes In Ap and Associated Alimentioning
confidence: 99%
“…At present, with the gradual progress of research, exosomes have been paid more and more attention. For example, umbilical cord mesenchymal stem cell-derived exosomes (ucMSC-Exs) were validated in our previous study to promote pancreatic tissue repair in traumatic pancreatitis injury by inhibiting pancreatic acinar cell apoptosis and controlling the systemic inflammatory response [ 13 ]. Kong et al [ 14 ] investigated the effect of cancer cell-derived exosomes linc00313 on M2 macrophage differentiation in non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%